Modeling exchange rate volatility in selected WAMZ countries: Evidence from symmetric and asymmetric GARCH models - Perekunah B. Eregha; Festus O. Egwaikhide; Emeka Osuji (SPOUDAI - Journal of Economics and Business, 2020)
Exchange rate is one of the macroeconomic indicators that gives concern to policy makers and investors as its movements are mostly unpredictable and tend to affect both trade and capital flows. Hence, this study analyzes exchange rate volatility clustering among selected WAMZ countries for the period 1980-2016. The univariate symmetric and asymmetric ARCH/GARCH modeling approach is employed with the Maximum Likelihood Estimation Technique and the results show exchange rate volatility clustering and the existence of leverage effect in all the countries. Therefore, it is imperative for policy makers in these countries to ensure adequate policy coordination based on current realities to boost investors' confidence and create needed automatic adjustment mechanism.
Keywords: E3; F30; F31; 330; Exchange Rate; Exchange Rate Volatility; Symmetric GARCH Models; Asymmetric GARCH Model; Leverage Effect